Singlet magnetism in intermetallic UGa2 unveiled by inelastic x-ray scattering - Marino, Andrea; Sundermann, Martin; Sacramento Christovam, Denise; Amorese, Andrea; Chang, Chun-Fu; Dolmantas, Paulius; Said, Ayman H.; Gretarsson, Hlynur; Keimer, Bernhard; Haverkort, Maurits W.; Andreev, Alexander V.; Havela, Ladislav; et al. (Physical review, 2023)
Using high resolution tender x-ray resonant inelastic scattering and hard x-ray nonresonant inelastic scattering beyond the dipole limit we were able to detect electronic excitations in intermetallic UGa2 that are highly atomic in nature. Analysis of the spectral lineshape reveals that the local 5f2 configuration characterizes the correlated nature of this ferromagnet. The orientation and directional dependence of the spectra indicate that the ground state is made of the Γ1 singlet and/or Γ6 doublet symmetry. With the ordered moment in the ab plane, we infer that the magnetism originates from the higher lying Γ6 doublet being mixed with the Γ1 singlet due to intersite exchange, qualifying UGa2 to be a true quantum magnet. The ability to observe atomic excitations is crucial to resolve the ongoing debate about the degree of localization versus itineracy in U intermetallics.